2002
DOI: 10.1016/s1097-2765(02)00740-2
|View full text |Cite
|
Sign up to set email alerts
|

ALL-1 Is a Histone Methyltransferase that Assembles a Supercomplex of Proteins Involved in Transcriptional Regulation

Abstract: ALL-1 is a member of the human trithorax/Polycomb gene family and is also involved in acute leukemia. ALL-1 is present within a stable, very large multiprotein supercomplex composed of > or =29 proteins. The majority of the latter are components of the human transcription complexes TFIID (including TBP), SWI/SNF, NuRD, hSNF2H, and Sin3A. Other components are involved in RNA processing or in histone methylation. The complex remodels, acetylates, deacetylates, and methylates nucleosomes and/or free histones. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
627
2
5

Year Published

2004
2004
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 665 publications
(654 citation statements)
references
References 59 publications
20
627
2
5
Order By: Relevance
“…It is believed that Mll controls Hox gene expression by binding to Hox regulatory elements and association with other transcriptional regulators. Indeed, MLL binding to the promoters of HOXA9 and Hoxc8 was described recently [Milne et al, 2002;Nakamura et al, 2002]. Overexpression of some Hox genes, including Hoxa9, has been linked to leukemia in mouse models.…”
Section: Wild-type Mll Functionmentioning
confidence: 99%
See 3 more Smart Citations
“…It is believed that Mll controls Hox gene expression by binding to Hox regulatory elements and association with other transcriptional regulators. Indeed, MLL binding to the promoters of HOXA9 and Hoxc8 was described recently [Milne et al, 2002;Nakamura et al, 2002]. Overexpression of some Hox genes, including Hoxa9, has been linked to leukemia in mouse models.…”
Section: Wild-type Mll Functionmentioning
confidence: 99%
“…Interestingly, just like the MLL protein, the Set1 complex was shown to methylate lysine 4 on histone H3 [Nagy et al, 2002]. This purified MLL complex is able to perform chromatin remodeling, histone methylation, acetylation, and deacetylation suggesting that all the associated proteins retain their enzymatic activities [Nakamura et al, 2002]. All the complex components bind to the promoter of HOXA9 only when MLL is present, showing the MLL-dependence of the whole supercomplex being targeted to the target gene region.…”
Section: The Story Is Two Complexmentioning
confidence: 99%
See 2 more Smart Citations
“…The ChIP methodology was recently applied to ALL-1 (Nakamura et al, 2002;Milne et al, 2002) and the protein was found bound at the promoters of HOX A9 and HOX C8 in cultured cells expressing these genes (homologues of Drosophila TREs and PREs have not been identified yet in mammals). Elimination of ALL-1, by applying interference RNA methodology, blocked transcription of HOX A9.…”
Section: Biological and Biochemical Activity Of All-1 And Its Drosophmentioning
confidence: 99%